Polymer compositions with improved storage stability

By using a polymer composition of a specific composition, the problem of insufficient PID resistance caused by the instability of photovoltaic module packaging materials in storage and transportation is solved, and the effect of high stability and long-term high-performance output is achieved.

CN115720550BActive Publication Date: 2025-03-28BOREALIS AG
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202180045929.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2021-06-21
Publication Date
2025-03-28
Estimated Expiration
2041-06-21

AI Technical Summary

Technical Problem

In the prior art, the packaging materials of photovoltaic modules exhibit instability during storage and transportation, resulting in insufficient potential induced attenuation (PID) resistance, affecting the long-term maximum power output (Pmax).

Method used

A polymer composition (I) is used that comprises an ethylene-vinyl acetate copolymer, a polyolefin elastomer or ethylene polymer, a ethylene copolymer containing silane groups, and a specific compound, through the specific proportions and combinations of these components, the storage and transport stability of the polymer is enhanced and the PID resistance of the photovoltaic module is enhanced.

Benefits of technology

The high stability of the polymer composition during storage and transportation is achieved, and the PID resistance of the photovoltaic module is significantly improved, thereby ensuring long-term high-performance output, especially the Pmax retention rate after 96 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FHA0000009198120000011
    Figure FHA0000009198120000011
  • Figure FHA0000009198120000031
    Figure FHA0000009198120000031
  • Figure FHA0000009198120000051
    Figure FHA0000009198120000051
Patent Text Reader

Abstract

The present invention relates to a polymer composition (I) comprising at least the following components: (A) 87.00 to 99.79 wt. % of a specific polymer, based on the total weight of the polymer composition (I), (B) 0.20 to 10 wt. % of a specific ethylene copolymer, based on the total weight of the polymer composition (I), and (C) 0.01 to 3.00 wt. % of a compound according to formula (a), based on the total weight of the polymer composition (I), wherein components (A), (B) and (C) add up to 100 wt. %. In addition, the present invention relates to a photovoltaic module comprising at least one layer comprising the polymer composition (I), a method for improving the storage stability and / or transport stability of a polymer (A), and the use of components (B) and (C) for improving the storage stability and / or transport stability of a polymer (A).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polymer composition (I) comprising at least (A) a specific polymer selected from polyolefin elastomers or specific ethylene polymers, (B) a specific ethylene copolymer and (C) a specific compound according to formula (a). In addition, the present invention relates to a photovoltaic module comprising at least one layer comprising the polymer composition (I), a method for improving the storage stability and / or transport stability of the polymer (A) and the use of components (B) and (C) for improving the storage stability and / or transport stability of the polymer (A).

[0002] The polymer composition (I) according to the invention is very suitable as encapsulation material for solar cells. Background Art

[0003] Polymer compositions suitable as encapsulation materials for solar cells are known in the prior art.

[0004] EP 2 144 301 A1 relates to a photovoltaic module comprising a solar cell element and an insulating material laminated to at least one side of the solar cell element, wherein the insulating material comprises an olefin copolymer comprising monomer units containing silane groups, a method for producing such a photovoltaic module and the use of an olefin copolymer comprising monomer units containing silane groups for producing an insulating layer of a photovoltaic module.

[0005] WO 2017 / 076629 A1 relates to a photovoltaic module (PV) and a lamination method for producing the PV module.

[0006] WO 2019 / 158520 A1 relates to a polymer composition, an article comprising the polymer composition, preferably an article comprising at least one layer element (LE) comprising the polymer composition, and a method for producing the article.

[0007] US2014 / 045990 A1 relates to an olefin-based ionomer resin composition, an encapsulant, a photoelectric device, and an optoelectronic device. The resin composition can be used as an encapsulant for various optoelectronic devices.

[0008] CN 108517188 A relates to a photovoltaic encapsulation material with high light transmittance. The photovoltaic encapsulation material is prepared by the following method: 100 parts by weight of a base resin or a graft-modified base resin of the photovoltaic encapsulation material, 0.01 to 20 parts by weight of a highly transparent resin with high light transmittance and / or high refractive index, and other additives are pre-mixed, and then melted, extruded, cast, film-formed, cooled, cut, and rolled.

[0009] The packaging materials known from the prior art do not exhibit very good storage and / or transport property stability.

[0010] Potential induced degradation (PID) is an undesirable effect on solar modules. PID, as the name implies, can occur when the module's voltage potential and leakage currents drive ion migration within the module between the module's semiconductor materials and other components (e.g., glass, mount, and frame), thereby causing the module's power output capability to degrade, in some cases significantly.

[0011] The use of polymer compositions known from the prior art as encapsulation materials does not allow photovoltaic modules to exhibit acceptable PID resistance. Summary of the invention

[0012] Starting from this, it is an object of the present invention to provide polymer compositions which have very good storage and / or transport stability and which additionally allow the manufacture of photovoltaic modules having increased PID resistance, thereby allowing high long-term P max , such as after 96 hours.

[0013] These objects have been achieved by a polymer composition (I) according to a first aspect of an embodiment of the present invention, the polymer composition (I) comprising at least the following components:

[0014] (A) 87.00 to 99.79 wt. % based on the total weight of the polymer composition (I) of a polymer selected from ethylene-vinyl acetate copolymers, polyolefin elastomers or ethylene polymers (a), wherein the ethylene polymers (a) are selected from

[0015] (a1) an ethylene copolymer having units containing a functional group;

[0016] (a2) ethylene copolymers comprising one or more polar comonomer units selected from (C1-C6)-alkyl acrylate or (C1-C6)-alkylacrylate comonomer units, optionally with units containing functional groups different from said polar comonomer units;

[0017] (a3) an ethylene copolymer comprising one or more α-olefin comonomer units; optionally with functional group-containing units different from the polar comonomer units of polymer (a2); or a mixture thereof; and

[0018] (b) units containing silane groups;

[0019] (B) 0.20 to 10.00 wt. % of an ethylene copolymer with functional group-containing units derived from at least one unsaturated carboxylic acid and / or anhydrides, metal salts, esters, amides or imides thereof and mixtures thereof, based on the total weight of the polymer composition (I), wherein component (B) is different from component (A);

[0020] (C) 0.01 to 3.00 wt. % of a compound according to formula (a), based on the total weight of the polymer composition (I);

[0021]

[0022] The total weight of components (A), (B) and (C) is 100 wt%.

[0023] Advantageous embodiments of the polymer composition (I) according to the invention are specifically defined in other embodiments of the invention. A second aspect of the embodiments of the invention relates to a photovoltaic module comprising at least one layer comprising the polymer composition (I) according to the invention, and other embodiments of the invention relate to specific embodiments of the photovoltaic module.

[0024] A third aspect of an embodiment of the present invention relates to a method for improving the storage stability and / or transportation stability of a polymer (A), and another embodiment of the present invention defines a specific embodiment of the method. A fourth aspect of an embodiment of the present invention relates to the use of components (B) and (C) for improving the storage stability and / or transportation stability of component (A), and a fifth aspect of an embodiment of the present invention relates to the use of a polymer composition (I) in a photovoltaic module. DETAILED DESCRIPTION

[0025] definition

[0026] Quantity

[0027] The polymer composition (I) according to the invention must contain components (A), (B) and (C), and optionally component (B2) and / or additive (D). The requirement applicable here is that the sum of components (A), (B) and (C) and, if present, component (B2) and / or additive (D) is 100 wt %. Fixed ranges for the amounts of the individual components (A), (B), (C) and optional components (B2) and / or additive (D) are to be understood as meaning that any amount for each of the individual components can be selected within the specified range, provided that the strict condition is met that the sum of all components (A), (B), (C) and optional components (B2) and / or additive (D) is 100 wt %.

[0028] An "element" in relation to the photovoltaic module of the present invention refers to a self-contained unit (also referred to as "self-contained unit") of the photovoltaic module. The elements of the photovoltaic module are preferably connected by lamination to form the photovoltaic module.

[0029] "Front" in connection with the photovoltaic module of the present invention refers to the planar side of the photovoltaic module that faces toward solar radiation.

[0030] "Back" in relation to the photovoltaic module of the present invention refers to the side of the photovoltaic module that faces away from the plane of solar radiation.

[0031] A "photovoltaic cell element" is an element in a photovoltaic module that converts the energy of light directly into electricity by the photovoltaic effect. Silicon-based materials such as crystalline silicon are a non-limiting example of materials for photovoltaic cells. As is well known to those skilled in the art, crystalline silicon materials can vary in crystallinity and crystal size. Alternatively, the photovoltaic cell element can be a substrate layer, on one surface of which another layer or deposit with photovoltaic activity is provided, such as a glass layer with a photovoltaically active ink material printed on one side thereof, or a substrate layer with a photovoltaically active material deposited on one side thereof. For example, in well-known thin film solutions for photovoltaic cell elements, for example, a photovoltaically active ink is printed on one side of a substrate, which is typically a glass substrate.

[0032] "Photovoltaic cell" refers herein to the layer elements of the photovoltaic cell as explained above, as well as the connectors.

[0033] "Rigid" in relation to the photovoltaic modules of the present invention means that the element is stiff and cannot bend in the same manner as a flexible element, and if bent, the integrity of the element is typically easily compromised, resulting in permanent fractures, unlike the case of flexible elements. A skilled person can easily distinguish between rigid layer elements and flexible layer elements.

[0034] Ethylene polymers herein refer to polymers comprising a majority by weight of ethylene monomer units (ie more than 50% by weight of ethylene monomer units).

[0035] "Comonomer" herein refers to a copolymerizable comonomer unit.

[0036] "Units containing silane groups" herein refer to chemical moieties containing one or more silane groups. "Units containing silane groups" may be a part of a polymer or compound different from the ethylene polymer (a). The polymer or compound containing silane groups is then added to the polymer composition by blending with the ethylene polymer (a). "Units containing silane groups" may be a part of the ethylene polymer (a). Therefore, "units containing silane groups" may be copolymerizable comonomer units or units that may be chemically grafted onto the ethylene polymer (a).

[0037] A "functional group-containing unit" herein refers to a substituent or chemical moiety that is responsible for the characteristic chemical reaction of the corresponding polymer or compound.

[0038] Keep P max It is measured according to IEC 60904. max The PV module is tested under standard test conditions (STC) from 1000W / m 2 The power generated by the flash pulse. According to the IV curve generated under the flash test, P max Obtained from the following equation, where I sc is the short-circuit current, V oc is the open circuit voltage, and FF is the fill factor.

[0039] P max =V oc *I sc *FF

[0040] Where the term "comprising" is used in the present description and claims, it does not exclude other unspecified elements of major or minor functional importance. For the purposes of the present invention, the term "consisting of" is considered to be a preferred embodiment of the term "comprising". If hereinafter a group is defined as comprising at least a certain number of embodiments, this is also to be understood as disclosing a group which preferably consists only of these embodiments.

[0041] Whenever the terms "including" or "having" are used, these terms are equivalent to "comprising" as defined above.

[0042] Where an indefinite or definite article is used when referring to a singular noun eg "a", "an" or "the", this includes the plural of that noun unless something else is specifically stated.

[0043] Component (A)

[0044] The polymer composition (I) according to the present invention comprises as component (A) 87.00 to 99.79 wt. %, based on the total weight of the polymer composition (I), a polymer selected from ethylene-vinyl acetate copolymers, polyolefin elastomers or ethylene polymers (a), the ethylene polymers (a) being selected from: (a1) ethylene copolymers with units containing functional groups; (a2) ethylene copolymers containing one or more polar comonomer units selected from (C1-C6)-alkyl acrylates or (C1-C6)-alkylacrylate (C1-C6)-alkyl ester comonomer units, which optionally carry units containing functional groups different from the polar comonomer units; (a3) ​​ethylene copolymers containing one or more α-olefin comonomer units; which optionally carry units containing functional groups different from the polar comonomer units of polymer (a2); or mixtures thereof; and (b) units containing silane groups.

[0045] Preferred embodiments of component (A) will be discussed below.

[0046] According to a preferred embodiment of the present invention, component (A) comprises and preferably consists of: (a1) an ethylene copolymer with units (b) containing silane groups as functional group-containing units; or (a2) an ethylene copolymer comprising one or more polar comonomer units selected from (C1-C6)-alkyl acrylates or (C1-C6)-alkylacrylate (C1-C6)-alkyl ester comonomer units, which optionally have units (b) containing silane groups as functional group-containing units different from the polar comonomer units.

[0047] Another preferred embodiment of the present invention provides that component (A) is (a1) an ethylene copolymer having a silane group-containing unit (b) as a functional group-containing unit; or (a2) an ethylene polymer comprising methyl acrylate comonomer units and having a silane group-containing unit (b) different from the polar comonomer units as a functional group-containing unit.

[0048] Another preferred embodiment of the present invention provides that component (A) is a copolymer (a1) of ethylene and vinyltrimethoxysilane comonomer units or a terpolymer (a2) of ethylene and methyl acrylate comonomer units and vinyltrimethoxysilane comonomer units. The content of methyl acrylate comonomer units present in the ethylene polymer (a2) is preferably in the range of 4.5 to 18 mol%, more preferably 5.0 to 18.0 mol%, still more preferably 6.0 to 18.0 mol%, even more preferably 6.0 to 16.5 mol%, even still more preferably 6.8 to 15.0 mol%, most preferably 7.0 to 13.5 mol%. The content of vinyltrimethoxysilane comonomer units (b) in the ethylene polymer (a2) is preferably in the range of 0.01 to 1.00 mol%, more preferably 0.05 to 0.80 mol% and still more preferably 0.10 to 0.60 mol%.

[0049] In another preferred embodiment of the present invention, component (A) is different from the polyolefin elastomer and / or the ethylene-vinyl acetate copolymer.

[0050] According to another preferred embodiment of the present invention, the content of component (A) in the polymer composition (I) is in the range of 92.50 to 99.45 wt %, preferably in the range of 95.0 to 98.9 wt % and more preferably in the range of 97.0 to 98.85 wt %, based on the total weight of the polymer composition (I).

[0051] According to another preferred embodiment of the present invention, the α-olefin comonomer of the ethylene polymer (a3) ​​is preferably selected from α-olefins having 3 to 12 carbon atoms, more preferably selected from α-olefins having 4 to 8 carbon atoms, such as 1-butene, 1-hexene or 1-octene.

[0052] In another preferred embodiment, the α-olefin comonomer content of the ethylene polymer (a3) ​​is preferably 4.5 to 18 mol%, preferably 5.0 to 18.0 mol%, preferably 6.0 to 18.0 mol%, preferably 6.0 to 16.5 mol%, more preferably 6.8 to 15.0 mol%, more preferably 7.0 to 13.5 mol%.

[0053] The units (b) containing silane groups and the polymer (a) may be present in the polymer composition of the present invention as separate components (i.e. as a blend). Alternatively, the units (b) containing silane groups may be present as a comonomer of the polymer (a) or as a compound chemically grafted onto the polymer (a). In general, the copolymerization and grafting of units containing silane groups with ethylene are well-known techniques and are well documented in the polymer field and are within the skill of the technician.

[0054] In the case of a blend, the silane group-containing unit (b) component can be a silane group-containing polymer or a silane group-containing compound. The silane group-containing compound can at least partially chemically react with the polymer (a), for example grafted to the polymer (a), optionally using, for example, a free radical former such as a peroxide. Such a chemical reaction can occur before or during the lamination process of the present invention.

[0055] Preferably, the silane group-containing unit (b) is present (bonded) in the polymer (a). More preferably, the polymer (a) carries a unit containing a functional group, wherein the unit containing a functional group is the silane group-containing unit (b). In this embodiment, the silane group-containing unit (b) can be copolymerized or grafted to the polymer (a). Therefore, as a preferred functional group-containing unit, the silane group-containing unit (b) is preferably present in the polymer (a) in the form of a comonomer unit or in the form of a grafted compound.

[0056] In a more preferred embodiment of the invention, polymer (a) comprises as a comonomer in polymer (a) a unit containing a functional group, which is a unit (b) containing a silane group. Copolymerization provides a more uniform incorporation of the unit (b). Furthermore, copolymerization does not require the use of peroxides, which are typically required to graft the units to polyethylene. It is known that peroxides bring limitations to the choice of MFR of polymers used as starting polymers for PV modules (the MFR of the polymer decreases during the grafting process because peroxides not only initiate grafting but also crosslink the polymer) and that decomposition products formed by peroxides may deteriorate the quality of the polymer.

[0057] The silane group-containing comonomer unit or compound as the silane group-containing unit (b) is suitably a hydrolyzable unsaturated silane compound represented by the formula

[0058] R1SiR2qY3-q(I)

[0059] in

[0060] R1 is an ethylenically unsaturated hydrocarbon group, a hydrocarbonoxy group or a (meth)acryloyloxy hydrocarbon group,

[0061] Each R2 is independently an aliphatic saturated hydrocarbon group,

[0062] Y, which may be the same or different, is a hydrolyzable organic group, and

[0063] q is 0, 1, or 2.

[0064] In one embodiment of the silane group-containing units (b) of the present invention, the comonomer / compound of formula (I) is selected from vinyltrimethoxysilane, vinylbismethoxyethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane. Vinyltrimethoxysilane is the most preferred.

[0065] The amount of the silane group-containing units (b) present in the polymer (a) is 0.01 to 1.00 mol %, preferably 0.05 to 0.80 mol %, more preferably 0.10 to 0.60 mol %, still more preferably 0.10 to 0.50 mol %.

[0066] The melt flow rate MFR2 (2.16 kg; 190°C) of the ethylene polymer (a) is preferably less than 20 g / 10 min, more preferably 0.1 to 15 g / 10 min, even more preferably 0.2 to 13 g / 10 min, still more preferably 0.3 to 13, most preferably 2.0 to 8.0 g / 10 min.

[0067] The density of the ethylene polymer (a) is preferably higher than 860 kg / m 3 Preferably, the density measured according to ISO 1872-2 is not higher than 970 kg / m 3 , more preferably 920 to 960 kg / m 3 .

[0068] The polymer (a) of the polymer composition may be, for example, commercially available or may be prepared according to or analogously to known polymerization processes described in the chemical literature. Further details on the production of ethylene (co)polymers by high-pressure free-radical polymerization may be found, for example, in Encyclopedia of Polymer Science and Engineering, Vol. 6 (1986) pp. 383-410 and Encyclopedia of Materials: Science and Technology, 2001 Elsevier Science Ltd.: "Polyethylene: High-pressure, R. Klimesch, D. Littmann and F.-O. Found in pp. 7181-7184.

[0069] Component (B)

[0070] In addition to components (A) and (C), the polymer composition (I) according to the present invention must also contain, as component (B), 0.20 to 10.00 wt. %, based on the total weight of the polymer composition (I), of an ethylene copolymer with functional group-containing units derived from at least one unsaturated carboxylic acid and / or its anhydride, metal salt, ester, amide or imide and mixtures thereof, wherein component (B) is different from component (A).

[0071] Preferred embodiments of component (B) will be discussed below.

[0072] In a preferred embodiment according to the present invention, component (B) is a copolymer of ethylene and a C4 to C10 alpha olefin comonomer, preferably a copolymer of ethylene and 1-octene; wherein the density of the copolymer measured according to ISO 1183 before the introduction of the functional groups is 850 kg / m 3 Up to 920kg / m 3 In the range of 860 to 905 kg / m 3 In the range of 865 to 905 kg / m 3 In the range of 890 to 910 kg / m 3 within the range.

[0073] According to another preferred embodiment of the present invention, it is provided that, before the introduction of the functional group, component (B) has an MFR2 measured at 190° C. and a load of 2.16 kg according to ISO 1133 in the range of 0.1 to 20.0 g / 10 min, preferably in the range of 0.5 to 10 g / 10 min and more preferably in the range of 6.0 to 8.0 g / 10 min.

[0074] According to another preferred embodiment of the present invention, it is provided that after the introduction of the functional group, component (B) has an MFR2 measured according to ISO 1133 at 190° C. and a load of 2.16 kg in the range of 0.1 to 10.0 g / 10 min, preferably in the range of 0.5 to 5 g / 10 min and more preferably in the range of 2.5 to 3.5 g / 10 min.

[0075] The C4 to C8 alpha-olefin comonomer is, for example, 1-butene, 1-hexene or 1-octene. Preferably, the comonomer is 1-butene or 1-octene, more preferably the comonomer is 1-octene. The amount of the comonomer is generally in the range of 20.0 wt % to 45.0 wt %, depending on the selected comonomer and the desired density. The ethylene content of suitable copolymer (a) is in the range of 55 to 80 wt %, preferably 58 to 78 wt % and more preferably 60 to 75 wt %.

[0076] According to another preferred embodiment of the present invention, the ethylene copolymer used for component (B) is a copolymer of ethylene and methyl acrylate or a copolymer of ethylene and butyl acrylate.

[0077] In another preferred embodiment according to the present invention, component (B) carries functional group-containing units derived from a compound selected from the group consisting of maleic anhydride, acrylic acid, methacrylic acid, crotonic acid, fumaric acid, fumaric anhydride, maleic acid, citraconic acid and mixtures thereof, preferably carries functional group-containing units derived from maleic anhydride.

[0078] According to another preferred embodiment of the present invention, component (B) is obtained by copolymerizing and / or grafting a copolymer with ethylene using a compound selected from the group consisting of maleic anhydride, acrylic acid, methacrylic acid, crotonic acid and mixtures thereof, wherein grafting using maleic anhydride is preferred.

[0079] Grafting can be by any method known in the art, as in the melt without solvent or in solution or dispersion or in fluidized bed. Typically, grafting is carried out in a heated extruder or mixer, as described in, for example, US3236917A, US 4639495 A, US 4950541 A or US 5194509 A. Typically, grafting is carried out in a twin screw extruder as described in US4950541A. Grafting can be carried out in the presence or absence of a free radical initiator, but is preferably carried out in the presence of a free radical initiator such as an organic peroxide, an organic perester or an organic hydroperoxide.

[0080] According to another preferred embodiment of the present invention, the content of the functional group-containing units derived from unsaturated carboxylic acid or carboxylic acid anhydride in component (B) is in the range of 0.01 to 2.0% by weight, preferably in the range of 0.02 to 1.5% by weight and more preferably in the range of 0.20 to 1.0% by weight.

[0081] Another preferred embodiment provides that component (B) is a copolymer of ethylene and 1-octene grafted with maleic anhydride, preferably the content of 1-octene is in the range of 20 to 45% by weight, preferably in the range of 22 to 42% by weight and more preferably in the range of 25 to 40% by weight and still more preferably in the range of 28 to 32% by weight, based on the total weight of the copolymer of ethylene and 1-octene, and the content of maleic anhydride is in the range of 0.01 to 2.0% by weight, preferably in the range of 0.02 to 1.5% by weight and more preferably in the range of 0.20 to 1.0% by weight, based on the total weight of component (B).

[0082] According to another preferred embodiment of the present invention, the melting point of component (B) is in the range of 30°C to below 100°C, preferably in the range of 30°C to below 90°C, more preferably in the range of 30°C to below 80°C and most preferably in the range of 30°C to below 70°C. According to another preferred embodiment of the present invention, the dispersion Mw / Mn of component (B) is most often below 4, such as 3.8 or lower, but at least 1.7. Preferably between 3.5 and 1.8.

[0083] Suitable base copolymers for component (B) (these are before the functional groups have been introduced) are commercially available, for example under the trade name Queo from Borealis AG, under the trade name Engage or Affinity from DOW or under the trade name Tafmer from Mitsui.

[0084] Alternatively, these base copolymers can be prepared by known methods in a one-stage or two-stage polymerization process (including solution polymerization, slurry polymerization, gas phase polymerization or a combination thereof) in the presence of a suitable catalyst known to those skilled in the art, such as a vanadium oxide catalyst or a single active site catalyst (e.g., a metallocene or a constrained geometry catalyst). Suitable methods are particularly described in WO 2019 / 201934 A1.

[0085] A known solution technology suitable for use in the method according to the invention is the BORCEED (formerly COMPACT) technology.

[0086] In another preferred embodiment according to the present invention, the content of component (B) in the polymer composition (I) is in the range of 0.5 to 5.0 wt. %, preferably in the range of 1.0 to 3.0 wt. % and more preferably in the range of 1.0 to 2.0 wt. %, based on the total weight of the polymer composition (I).

[0087] Optional component (B2)

[0088] In addition to the essential components (A) to (C), the polymer composition (I) according to the invention may comprise a component (B2) which is a copolymer of ethylene and (meth)acrylic acid. In a preferred embodiment, the optional component (B2) is a copolymer of ethylene and methacrylic acid.

[0089] The copolymer of ethylene and (meth)acrylic acid may be a copolymer prepared using (meth)acrylic acid in an amount ranging from 1 to 25 wt%, preferably 3 to 20 wt%, and more preferably 5 to 15 wt%, based on the total weight of the copolymer. For example, the copolymer of ethylene and (meth)acrylic acid may be prepared using (meth)acrylic acid in an amount ranging from 8 to 10 wt%, such as 9 wt%. Thus, the (meth)acrylic acid content of the copolymer may be in the range of 8 to 10 wt%, based on the total weight of the copolymer.

[0090] The copolymer of ethylene and (meth) acrylic acid may have an MFR2 in the range of 0.2 to 10.0 g / 10 min, preferably in the range of 0.5 to 5 g / 10 min and more preferably in the range of 1.5 to 3.5 g / 10 min, measured at 190° C. and a load of 2.16 kg according to ISO 1133. For example, the copolymer of ethylene and (meth) acrylic acid may have an MFR2 in the range of 2.0 to 3.0 g / 10 min, for example 2.5 g / 10 min.

[0091] In one embodiment, the melting point of the copolymer of ethylene and (meth)acrylic acid is in the range of 75 to 125°C, and preferably in the range of 90 to 110°C.

[0092] According to a preferred embodiment, optional component (B2) is a copolymer of ethylene and methacrylic acid, wherein the copolymer is prepared using methacrylic acid in an amount in the range of 1 to 25 wt%, preferably 3 to 20 wt%, and more preferably 5 to 15 wt%, wherein the copolymer has an MFR2 measured according to ISO 1133 at 190°C and a load of 2.16 kg in the range of 0.2 to 10.0 g / 10 min, preferably in the range of 0.5 to 5 g / 10 min and more preferably in the range of 1.5 to 3.5 g / 10 min, and wherein the melting point of the copolymer is in the range of 75 to 125°C, and preferably in the range of 90 to 110°C.

[0093] The copolymer of ethylene and (meth) acrylic acid may be present in composition (I) in an amount ranging from 0.05 to 5 wt%, preferably from 0.10 to 2.5 wt%, and more preferably from 0.10 to 1.5 wt%, based on the total weight of the composition. For example, the copolymer of ethylene and (meth) acrylic acid may be present in composition (I) in an amount ranging from 0.05 to 0.5 wt%, or in an amount ranging from 0.75 to 1.5 wt%.

[0094] Suitable as optional component (B2) is NUCREL TM 0903, which is commercially available from Dow DuPont.

[0095] Component (C)

[0096] In addition to components (A) and (B), the polymer composition (I) according to the present invention necessarily comprises, as component (C), from 0.01 to 3.00 wt. %, based on the total weight of the polymer composition (I), a compound according to formula (a),

[0097]

[0098] in:

[0099] R1, R 1’ , R2 and R 2’ are each independently selected from the group consisting of hydrogen, n-alkyl, isoalkyl, alkoxy, cycloalkyl, alkenyl, halogen, and mixtures thereof; and

[0100] X is selected from the group consisting of primary amines, secondary amines, tertiary amines, hydrogen, alkyl groups, alkenyl groups, and mixtures thereof.

[0101] Preferred embodiments of component (C) will be discussed below.

[0102] According to a preferred embodiment of the present invention, component (C) is a compound represented by formula (a); wherein R1 and R 1’ are each independently a n-alkyl group, preferably having 3 to 9 carbon atoms, more preferably R1 and R 1’ The same and most preferably R1 and R 1’ is n-butyl; and / or R2 and R 2’ are each independently a n-alkyl or cycloalkyl group, more preferably R2 and R 2’ is a cycloalkyl group, still more preferably R2 and R 2’ The same and most preferably R2 and R 2’ is cyclohexyl; and / or X is selected from the group consisting of secondary and tertiary amines, preferably having 1 to 8 secondary and / or tertiary amino groups and more preferably having 4 amino groups.

[0103] According to a further preferred embodiment of the present invention, it is provided that the molecular weight of component (C) is in the range of 1000 to 2800 g / mol, preferably in the range of 2000 to 2600 g / mol and more preferably in the range of 2100 to 2300 g / mol.

[0104] According to another preferred embodiment of the present invention, component (C) is a compound having the following formula (b):

[0105]

[0106] The compounds according to formula (b) are marketed under the trade name NOR 116 is commercially available from BASF SE.

[0107] In another preferred embodiment of the present invention, the content of component (C) in the polymer composition (I) is in the range of 0.05 to 2.50 wt %, preferably in the range of 0.15 to 1.00 wt % and more preferably 0.15 to 1.00 wt %, based on the total weight of the polymer composition (I).

[0108] Without being bound by any theory, it is believed that component (C) is able to bind sodium ions (which contribute significantly to PID) as a chelate (see below).

[0109]

[0110] additive

[0111] According to a preferred embodiment of the present invention, the polymer composition (I) comprises at least one additive (D) selected from the group consisting of metal deactivators, nucleating agents, clarifiers, optical brighteners, acid scavengers, slip agents, pigments, fillers and flame retardants, tackifiers, plasticizers, crosslinkers, crosslinking enhancers, wavelength converters and mixtures thereof.

[0112] According to another preferred embodiment of the present invention, the content of the additive (D) is in the range of 0.0001 to 10 wt. %, preferably in the range of 0.01 to 5.0 wt. % and more preferably in the range of 0.1 to 2.5 wt. %, based on the total weight of the polymer composition (I).

[0113] The additives may be added in the form of a masterbatch, the content ranges specified above relate to the pure additives.

[0114] Polymer composition (I)

[0115] The polymer composition (I) according to the present invention necessarily comprises components (A), (B) and (C).

[0116] According to a preferred embodiment of the present invention, the content of component (A) in the polymer composition (I) is in the range of 92.50 to 99.45 wt %, preferably in the range of 95.0 to 98.9 wt % and more preferably in the range of 97.00 to 98.85 wt %, based on the total weight of the polymer composition (I).

[0117] In another preferred embodiment of the present invention, the content of component (B) in the polymer composition (I) is in the range of 0.50 to 5.00 wt. %, preferably in the range of 1.00 to 3.00 wt. % and more preferably in the range of 1.00 to 2.00 wt. %, based on the total weight of the polymer composition (I).

[0118] Another preferred embodiment of the present invention provides that the content of component (C) in the polymer composition (I) is in the range of 0.05 to 2.50 wt. %, preferably in the range of 0.10 to 2.00 wt. % and more preferably in the range of 0.15 to 1.00 wt. %, based on the total weight of the polymer composition (I).

[0119] In another preferred embodiment according to the invention, the polymer composition (I) is not crosslinked in the presence of a peroxide or a silanol condensation catalyst selected from carboxylates of tin, zinc, iron, lead or cobalt or aromatic organic sulfonic acids.

[0120] Another preferred embodiment of the present invention provides that the polymer composition (I) comprises the following components:

[0121] (A) a terpolymer (a2) of 96.50 to 98.99 wt.% of ethylene with methyl acrylate comonomer units and vinyltrimethoxysilane comonomer units;

[0122] (B) 1.00 to 3.00 weight percent of a copolymer of ethylene and a C4 to C10 alpha olefin comonomer, and

[0123] (C) 0.01 to 0.50 wt. % of a compound according to formula (a), wherein R1 and R 1’ are each independently a n-alkyl group, preferably having 3 to 9 carbon atoms, more preferably R1 and R 1’ The same and most preferably R1 and R 1’ is n-butyl; and R2 and R 2’ are each independently a n-alkyl or cycloalkyl group, more preferably R2 and R 2’ is a cycloalkyl group, more preferably R2 and R 2’ The same and most preferably R2 and R 2’ is a cyclohexyl group; and X is selected from the group consisting of secondary and tertiary amines, preferably having 1 to 8 secondary and / or tertiary amino groups and more preferably having 4 amino groups.

[0124] According to another preferred embodiment of the present invention, the polymer composition (I) comprises the following components: (A) 96.50 to 96.99 wt% of a terpolymer (a2) of ethylene with methyl acrylate comonomer units and vinyltrimethoxysilane comonomer units; (B) 1.00 to 3.00 wt% of a copolymer of ethylene with a C8 alpha olefin comonomer and (C) 0.01 to 0.5 wt% of a compound according to formula (b).

[0125] According to another preferred embodiment, the polymer composition (I) comprises and preferably consists of components (A), (B), (C) and optionally additives (D).

[0126] In a preferred embodiment of the present invention, the polymer composition (I) further comprises a component (B2). In case the optional component (B2) is present in the polymer composition (I) according to the present invention, the component (B2) is different from components (A) and (B).

[0127] The polymer composition (I) may comprise component (B2) in an amount ranging from 0.05 to 5 wt%, preferably 0.10 to 2.5 wt%, and more preferably 0.10 to 1.5 wt%, based on the total weight of the composition.

[0128] According to a preferred embodiment, the polymer composition (I) comprises the following components:

[0129] (A) 94.50 to 98.99 weight percent of a terpolymer (a2) of ethylene with methyl acrylate comonomer units and vinyltrimethoxysilane comonomer units;

[0130] (B) 0.25 to 3.00 wt%, preferably 1.00 to 3.00 wt%, of a copolymer of ethylene and a C4 to C10 alpha olefin comonomer;

[0131] (B2) 0.10 to 2.5 wt. % of a copolymer of ethylene and methacrylic acid, and

[0132] (C) 0.01 to 0.50 wt. % of a compound according to formula (a), wherein R1 and R 1’ are each independently a n-alkyl group, preferably having 3 to 9 carbon atoms, more preferably R1 and R 1’ The same and most preferably R1 and R 1’ is n-butyl; and R2 and R 2’ are each independently a n-alkyl or cycloalkyl group, more preferably R2 and R 2’ is a cycloalkyl group, more preferably R2 and R 2’ The same and most preferably R2 and R 2’is a cyclohexyl group; and X is selected from the group consisting of secondary and tertiary amines, preferably having 1 to 8 secondary and / or tertiary amino groups and more preferably having 4 amino groups.

[0133] According to another preferred embodiment of the present invention, the polymer composition (I) comprises the following components:

[0134] (A) 94.50 to 98.99 weight percent of a terpolymer (a2) of ethylene with methyl acrylate comonomer units and vinyltrimethoxysilane comonomer units;

[0135] (B) 0.25 to 3.00 wt%, preferably 1.00 to 3.00 wt%, of a copolymer of ethylene and a C4 to C10 alpha olefin comonomer;

[0136] (B2) 0.10 to 2.5% by weight of a copolymer of ethylene and methacrylic acid, and

[0137] (C) 0.01 to 0.50 wt. % of a compound according to formula (b).

[0138] According to another preferred embodiment, the polymer composition (I) comprises and preferably consists of components (A), (B), (B2), (C) and optionally additives (D).

[0139] Photovoltaic modules

[0140] The present invention also relates to a photovoltaic module comprising at least one layer comprising the polymer composition (I) according to the present invention. Preferably, the layer comprising and preferably consisting of the polymer composition (I) is an encapsulation layer.

[0141] According to yet another preferred embodiment of the present invention, the photovoltaic module comprises a front encapsulation layer element and a rear encapsulation layer element, wherein at least one of these encapsulation layer elements and preferably both encapsulation layer elements comprises and more preferably consists of polymer composition (I).

[0142] According to a preferred embodiment of the present invention, the photovoltaic module has a retention P measured according to IEC 60904. max It is higher than 95%, preferably in the range of 95 to 100% and more preferably in the range of 97 to 99.5%.

[0143] As is known in the art, the elements and layer structure of the photovoltaic modules of the present invention may vary depending on the desired module type.The photovoltaic modules may be flexible or rigid.In a preferred embodiment, the photovoltaic module is a rigid photovoltaic module.

[0144] In another preferred embodiment of the invention, the protective front layer element is a rigid protective front layer element, preferably a front glass layer element, and / or the protective back layer element is a rigid protective back layer element, preferably a back glass layer element.

[0145] According to another preferred embodiment of the present invention, the protective backing element is a polymer backsheet. The polymer material is preferably selected from the group consisting of polyethylene terephthalate, polyvinylidene fluoride, polyvinyl fluoride and polypropylene.

[0146] The photovoltaic modules of the present invention can be produced in a manner well known in the field of photovoltaic modules. The polymer layer elements can be produced in a conventional manner by extrusion, preferably by coextrusion or cast film extrusion, for example using conventional extruders and film-forming equipment. The layers of any multilayer element and / or any adjacent layers between two layer elements can be partially or completely coextruded or laminated.

[0147] The different elements of a photovoltaic module are typically assembled in a conventional manner to produce the final photovoltaic module. The elements may be provided individually to such an assembly step, or, for example, two elements may be in fully or partially integrated form, as is well known in the art. The different element components may then be attached together by lamination using conventional lamination techniques in the art. The assembly of photovoltaic components is well known in the field of photovoltaic modules.

[0148] All preferred aspects and embodiments as described above for the polymer composition (I) also apply to the photovoltaic module according to the invention.

[0149] method

[0150] The present invention also relates to a method for improving the storage stability and / or transportation stability of a polymer (A), comprising the following steps:

[0151] a) providing a polymer (A) selected from ethylene-vinyl acetate copolymers, polyolefin elastomers or ethylene polymers (a), wherein the ethylene polymers (a) are selected from

[0152] (a1) an ethylene copolymer having units containing a functional group;

[0153] (a2) ethylene copolymers comprising one or more polar comonomer units selected from (C1-C6)-alkyl acrylates or (C1-C6)-alkylacrylate (C1-C6)-alkyl ester comonomer units, optionally with units containing functional groups different from said polar comonomer units;

[0154] (a3) an ethylene copolymer comprising one or more α-olefin comonomer units; optionally with functional group-containing units different from the polar comonomer units of polymer (a2); or a mixture thereof; and

[0155] (b) units containing silane groups;

[0156] b) providing an ethylene copolymer (B) having functional group-containing units derived from at least one unsaturated carboxylic acid and / or anhydrides, metal salts, esters, amides or imides thereof and mixtures thereof, wherein component (B) is different from component (A);

[0157] c) providing a compound according to formula (a);

[0158]

[0159] d) mixing the polymer (A) with the compounds (B) and (C) to obtain a stabilized polymer composition (I).

[0160] Steps a) to c) may be performed in any order.

[0161] According to a preferred embodiment of the present invention, component (A) comprises and preferably consists of: (a1) an ethylene copolymer having a unit (b) containing a silane group as a functional group-containing unit; or (a2) an ethylene polymer comprising methyl acrylate comonomer units and having a unit (b) containing a silane group as a functional group-containing unit different from the polar comonomer units.

[0162] In another preferred embodiment according to the present invention, component (B) is a copolymer of ethylene and a C4 to C10 alpha olefin comonomer, preferably a copolymer of ethylene and 1-octene; wherein the copolymer has (i) a carbonyl group at 850 kg / m2 measured according to ISO 1183 before the introduction of the functional groups; 3 Up to 920kg / m 3 In the range of 865 to 905 kg / m 3 In the range of 865 to 910 kg / m 3 and more preferably in the range of 890 to 910 kg / m 3 density within the range of; and / or

[0163] (ii) MFR2 in the range of 0.1 to 20.0 g / 10 min, preferably in the range of 0.5 to 10 g / 10 min and more preferably in the range of 6.0 to 8.0 g / 10 min, measured according to ISO 1133 at 190°C and a load of 2.16 kg.

[0164] According to another preferred embodiment of the present invention, component (C) is a compound having the following formula (b):

[0165]

[0166] All preferences and embodiments as described above for components (A) to (C) shall also apply to the process according to the invention.

[0167] Use of components (B) and (C)

[0168] A further aspect of the present invention relates to the use of components (B) and (C) as defined above for improving the storage stability and / or transport stability of component (A) as defined above.

[0169] All preferred aspects and embodiments as described above for components (A) to (C) also apply to the use as stabilizer.

[0170] Use of polymer composition (I)

[0171] The invention also relates to the use of the polymer composition (I) in at least one layer of a photovoltaic module.

[0172] All preferred aspects and embodiments as described above for the polymer composition (I) also apply to the use in at least one layer of a photovoltaic module.

[0173] The invention will now be described with reference to the following non-limiting examples.

[0174] Experimental Section

[0175] A. Measurement Method

[0176] Unless defined otherwise, the following definitions of terms and determination methods apply to the above general description of the invention as well as to the following examples.

[0177] Melt flow rate

[0178] The melt flow rate (MFR) is determined according to ISO 1133 - Determination of melt mass-flow rate (MFR) and melt volume-flow rate (MVR) of thermoplastics - Part 1: Standard method and is expressed in g / 10 min. The MFR is an indicator of the flowability of the polymer and therefore also of the processability of the polymer. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR2 of polyethylene is determined at a temperature of 190°C and a load of 2.16 kg.

[0179] density

[0180] The density of the polymers was measured according to ISO 1183-2. The sample preparation was carried out according to ISO 1872-2 Table 3Q (compression moulding).

[0181] Comonomer content

[0182] The content (weight % and mole %) of polar comonomers present in the ethylene copolymer (component (A)) and the content (weight % and mole %) of units containing silane groups present in the copolymer are determined as described in WO 2018 / 141672 A1 for the content (weight % and mole %) of polar comonomers present in polymer (a) and the content (weight % and mole %) of units containing silane groups (preferably comonomers) present in polymer (a).

[0183] The α-olefin comonomer content present in the ethylene copolymer (component (B)) is determined as described in WO 2019 / 134904 for the quantification of the comonomer content of poly(ethylene-co-1-octene) copolymers.

[0184] Dynamic shear measurement (frequency sweep measurement)

[0185] Dynamic shear measurements were performed as described in WO 2018 / 141672 A1.

[0186] Melting temperature (Tm), crystallization temperature (Tc), heat of fusion (ΔH 熔融 ), crystallization enthalpy (ΔH 结晶 ) and crystallinity Tm, Tc, ΔH 熔融 and ΔH 结晶 The measurements were performed using a TA Instrument Q200 Differential Scanning Calorimetry (DSC) on 5 to 7 mg samples. The DSC was run according to ISO 11357 / Part 3 / Method C2 in a heating / cooling / heating cycle over a temperature range of -30 to +225°C at a scanning rate of 10°C / min. The crystallization temperature (Tc) and the crystallization enthalpy (H 结晶 ) is determined from the cooling step, while the melting temperature (Tm) and heat of fusion (H 熔融 ) is determined by the second heating step. The crystallinity is determined by assuming that the H of fully crystalline polypropylene 熔融 The value is 209 J / g and is calculated from the heat of fusion (see Brandrup, J., Immergut, EH eds. Polymer Handbook 3rd ed., Wiley, New York, 1989; Chapter 3).

[0187] FTIR

[0188] FTIR was used to determine the content of grafting agent (maleic anhydride) in polymer A.

[0189] Sample preparation

[0190] A small amount of sample (granules) was compression extruded (*) into a film / plate (thickness 0.5 mm) using a compression die and the following conditions.

[0191] (*) Extrusion / molding

[0192] 4 minutes at 180°C ("free melt", no applied pressure), 2 minutes at 180°C under pressure (-45 kN), 2 minutes cooling under pressure.

[0193] FTIR, calculation

[0194] IR spectra from films / plates were measured on a Bruker Tensor 27. Peak intensities (relative to baseline) were recorded; at -1782-1797 cm -1 (Baseline 1847cm -1 ) between 2641 and 2707 cm -1 (Baseline 2450cm -1 ) reference peak. The value from component / reference is calculated and compared with the calibration curve, which gives the total maleic anhydride content in the polymer. The maleic anhydride content in the calibration standard has been determined using the titration method described below.

[0195] Sample preparation for titration

[0196] Mix the sample thoroughly. The sample is in the form of particles.

[0197] Blind test

[0198] When heating xylene and dissolving the sample, close the container loosely with a ground glass stopper to allow pressure to equalize and prevent the solution from splashing out of the bottle. For example, a piece of paper or a thin wire can be sandwiched between the neck of the bottle and the ground cap to prevent the cap from sticking.

[0199] To 50 ml of xylene with a little antioxidant were added a few drops of phenolphthalein indicator. The resulting solution was then heated with a magnetic stirrer (>100°C) and thermotitrated with 0.02N KOH / IPA solution. The color change was noted: colorless => red (transparent).

[0200] Titrate the absorbance indicator and continue titrating until the color remains stable for about 10 seconds. Record the amount consumed.

[0201] Procedure for samples

[0202] About 600 to 800 mg of sample particles are weighed into an Erlenmeyer flask, and then 50 ml of xylene with a little antioxidant (to prevent oxidation of the product during processing) and a magnetic stirring bar are added to the flask. Next, the flask is stoppered and transferred to a heated magnetic stirrer located in a fume hood. The sample is dissolved. The sample takes about 15 minutes to dissolve. Then a few drops of phenolphthalein indicator are added. The sample is hot titrated with 0.02N KOH / IPA solution (>100°C). Record the consumption. Note the color change: colorless=>red (transparent).

[0203] calculate

[0204] Total acid content (wt%) = (((Vn-Vs) x N x E(acid)) / W) x 100

[0205] in:

[0206] N = normalization of titration solution (mekv / ml) W = sample weight (g)

[0207] Vn = sample consumption (ml) Vs = blind test consumption (ml)

[0208] E = equivalent acid weight (g / mekv)

[0209] E = (maleic acid) = 0.116 / 2 = 0.058

[0210] E=(maleic anhydride)=0.098

[0211] The results are expressed as weight percent to two decimal places (X.xx).

[0212] PID test

[0213] The PID stress test was performed on a 1-cell PV module prepared as described below, according to the foil method as described in IEC62804-1: "Test method for detecting potential-induced degradation of crystalline silicon photovoltaic (PV) modules". The foil method was applied, using a Memmert CTC256 climate chamber with a temperature of 85°C and a relative humidity of 85% (controlled, stable) environmental stress conditions during the entire test. A potential difference of 1000V was applied between the aluminum (Al) foil and the short-circuited solar cell. During the PID stress, the solar cell was at a negative potential (-1000V) relative to the aluminum foil (0V). Therefore, positive charges were pushed towards the solar cell. The 1-cell module laminate was placed under double-sided PID stress, i.e. the aluminum foil, which was at a high voltage difference with the solar cell, was attached to the front and rear SLG cover plates. The test duration of the PID test was 96h.

[0214] Flash Test

[0215] For all 1-cell modules, a pv-tools Halm certis PV-OS system was used to quantify the PV power loss under PID stress. All characterization measurements were performed using single-sided illumination and a black cloth underneath the laminate to reduce reflected irradiance from the front and back sides of the single-cell laminate. Power output loss was calculated as P after 96 h PID testing. max All IV characterizations are done in accordance with IEC 60904.

[0216] B. Starting Materials

[0217] Preparation of polymer 1 (copolymer of ethylene with methyl acrylate comonomer and vinyltrimethoxysilane comonomer)

[0218] The copolymer of ethylene with methyl acrylate comonomer and vinyl trimethoxysilane comonomer (Polymer 1) is produced in a commercial high pressure tubular reactor using a conventional peroxide initiator at a pressure of 2500 to 3000 bar and a maximum temperature of 250 to 300° C. Ethylene monomer, methyl acrylate (MA) polar comonomer and vinyl trimethoxysilane (VTMS) comonomer are added to the reactor system in a conventional manner. Chain transfer agents are used to adjust the melt flow rate as is well known to the skilled person. Having information about the desired balance of properties of the final polymer 1, the skilled person can control the process to obtain polymer 1.

[0219] Table 1 gives the amount of vinyltrimethoxysilane units, VTMS, the amount of methyl acrylate, MA and MFR2.

[0220] The properties in Table 1 were measured on polymer 1 obtained from the reactor.

[0221] Table 1: Product properties of polymer 1.

[0222] Properties of the polymer obtained from the reactor Polymer 1 MFR2.16, g / 10min 4.5 Methyl acrylate content, mole % (weight %) 8.6(22) Melt temperature, °C 90 VTMS content, mole % (weight %) 0.38(1.7) <![CDATA[Density, kg / m 3 > 946 SHI(0.05 / 300), 150℃ 52

[0223] In Table 1 above and below, MA indicates the content of methyl acrylate comonomer present in the polymer and correspondingly VTMS content indicates the content of vinyltrimethoxysilane comonomer present in the polymer.

[0224] Polymer A (copolymer of ethylene and 1-octene grafted with maleic anhydride)

[0225] As the base polymer, Queo TM 0207LA. Queo TM0207LA is an ethylene-based 1-octene elastomer (with an MFR2 (2.16 kg, 190°C) of 6.5 g / 10 min and a density of 902 kg / m 3 ), and is commercially available from Borealis AG, Austria.

[0226] The base polymer was grafted with maleic anhydride on a Coperion ZSK32 (screw diameter d=32 mm) co-rotating twin-screw extruder (length 48 L / d) connected to a BKG underwater pelletizer (UP). A Piovan cooler was used to reduce the UP process water temperature to 12°C. The MAH agglomerates were "ground" and mixed with the cryogenically ground base polymer in a high-speed Mixaco mixer (1:6=1 part MAH, 5 parts base polymer). This "dilution" prevented re-agglomeration of the MAH and allowed accurate feeding of only 0.6% by weight of the modifier. For this purpose, a production line additive feeder equipped with an agitator was used.

[0227] Queo0207LA was grafted by adding different amounts of maleic anhydride (MAH).The peroxide initiator (0.1 wt% POX-Perkadox 14S-fl, Akzo Nobel) was fed as a 10% solution in isododecane.

[0228] The dry blend of Queo 0207LA and MAH was fed to the feed section of the extruder through a hopper. The POX solution was fed to the side feed port into the feed section of the extruder. The screw speed was 200 rpm and the throughput was 8 kg / h.

[0229] The residence time was 60 seconds. This resulted in a grafted maleic anhydride content of 1.05% by weight, based on the total weight of polymer A, as determined by FTIR. The MFR2 (2.16 kg, 190° C.) of the grafted material was 2.99 g / 10 min.

[0230] Nucrel 0903

[0231] NUCREL TM 0903 is a copolymer of ethylene and methacrylic acid, made with nominally 9 wt% methacrylic acid. MFR (190°C, 2.6 kg) is 2.5 g / 10 min, and the melting point is 101°C. NUCREL TM 0903 supplied by Dow DuPont.

[0232] Stabilizer

[0233] Flamestab NOR-116: Commercially available from BASF CAS: 191680-81-6

[0234] Sabostab UV62: Commercially available from BASF CAS: 65447-77-0

[0235] Sabostab UV70: Commercially available from BASF CAS: 52829-07-9

[0236] Sabostab UV94: Commercially available from BASF CAS: 70624-18-9

[0237] C. Preparation of polymer compositions, films thereof and photovoltaic modules (PV modules)

[0238] a) Polymer composition

[0239] Table 2 shows the composition of the polymer compositions according to comparative examples CE1 to CE4 and inventive example IE1. These polymer compositions are obtained by blending polymer 1 with commercially available stabilizers and / or polymer A.

[0240] Table 2A: Polymer compositions CE1 to CE4 and IE1.

[0241] Components unit CE1 CE2 CE3 CE4 IE1 Polymer 1(A) weight% 98 98 99 98 96 Polymer A(B) weight% - - - - 2 <![CDATA[Sabostab UV62 MB a ]]> weight% 2 - - - - Sabostab UV62 ppm 1570 - <![CDATA[Sabostab UV70 / Sabostab UV94 MB b ]]> weight% - 2 1 - - Sabostab UV70 ppm - 1250 625 - - Sabostab UV94 ppm - 312 156 - - <![CDATA[Flamestab NOR-116MB c (C)]]> weight% - - - 2 2 Flamestab NOR-116(C) ppm - - - 1570 1570

[0242] a MB contains 92.15 EMA copolymer (24% MA, MFR2 (190°C) = 2.0 g / 10 min) and 7.85% stabilizer;

[0243] b MB contains 92.15 EMA copolymer (24% MA, MFR2 (190°C) = 2.0 g / 10 min) and 7.85% stabilizer;

[0244] c MB contained 92.15 EMA copolymer (24% MA, MFR2 (190° C.)=2.0 g / 10 min) and 7.85% stabilizer.

[0245] Table 2B: Polymer compositions IE2 to IE5

[0246] Components unit IE2 IE3 IE4 IE5 Polymer 1(A) weight% 97.25 96.25 96.25 95.25 Polymer A(B) weight% 0.5 0.5 1.5 1.5 Nucrel 0903(B2) weight% 0.25 1.25 0.25 1.25 <![CDATA[Flamestab NOR-116MB c (C)]]> weight% 2 2 2 2

[0247] b) Films used for storage stability testing

[0248] For the storage stability tests described in section D below, films consisting of polymer compositions CE1 to CE4 and IE1 (test 1) and films consisting of polymer compositions IE2 to IE5 (test 2) were produced.

[0249] These films are produced on a Dr.Collin cast film line. First, the material enters the extruder, through a nozzle into an embossing roll, and finally into two cooling rolls. The temperature of the extruder and nozzle is at 145°C and the feed rate is 7.5 kg / m. The cooling roll cools the film to 25°C at about 1.10 m / min. The film thickness is 480 μm thick when the process is completed, with embossing on one side of the film with a depth of 100 μm. The embossing roll is from UNGRICHT GMBH+CO KG, where the roll manufacturer is from DrCollin GmbH, and is cooled by water. The embossing of the film improves the lamination properties and rewinding of the film.

[0250] c) Preparation of photovoltaic modules

[0251] c1) Preparation of packaging layer components

[0252] Encapsulating layer elements made of polymer compositions CE1 to CE4 and IE1 (having dimensions of 995 mm wide and 0.45 mm thick) were produced on a Dr. Collin cast film line using a melt temperature of 145°C and a line speed of 7.5 kg / h.

[0253] c2) Preparation of PV modules

[0254] Protective front layer element: Glass layer, structured solar glass, SIH, supplied by Inter Float, length: 200 mm and width: 300 mm, total thickness 3.2 mm.

[0255] Front and rear encapsulating elements: films of polymer compositions CE1 to CE4 and IE1 as described above, having the same width and length dimensions as the protective front and rear layer elements, each having a total thickness of 0.45 mm.

[0256] PV cell element: 1 welded bifacial solar cell, cell size 156*156mm, obtained from Trina Solar, pseudo-square, 5 busbars, total thickness 200 microns.

[0257] Protective backing element: Glass layer, structured solar glass, SIH, supplied by Inter Float, length: 200 mm and width: 300 mm, total thickness 3.2 mm.

[0258] Two PV module assemblies were prepared for each encapsulation layer element as follows. Before placing the first encapsulation layer element film on the solar glass, the front protective glass element was cleaned with isopropyl alcohol. The solar glass element had the following dimensions: 200mm x300mm x 3.2mm (b*l*d). The front encapsulation layer element was cut to the same size as the solar glass element. After placing the front encapsulation layer element on the front protective glass element, the welded solar cells were then placed on the front encapsulation layer element. Further, a rear encapsulation layer element was placed on the obtained PV cell element, and the back protective glass element was cleaned with isopropyl alcohol before placing the back protective glass element on the rear encapsulation layer element. The obtained PV module assembly then underwent a lamination process as described below.

[0259] Lamination process:

[0260] Laminator: L036LAB, supplied by Siemens.

[0261] Each PV module assembly sample was laminated in a L036LAB laminator from Siemens, with the laminator temperature settings and pressure settings appropriate for the encapsulation layer elements. The lamination settings are given in Table 3.

[0262] Table 3: Lamination settings for PV modules 1 to 5.

[0263] Module 1 Module 2 Polymer composition for encapsulation layer element IE1 IE1 Temperature, [℃] 150 150 Pressure [mbar] 800 800 Total time of the step [s] <![CDATA[1200 a ]]> <![CDATA[1200 a ]]>

[0264] a) 300 s melting phase and 900 s pressing phase.

[0265] The 1-cell photovoltaic module prepared according to the lamination process described above is Figure 1 It is shown in Figure 1 The layer elements (separated) of a photovoltaic module are shown, namely a protective front layer element (1), a front encapsulation layer element (2), a photovoltaic cell element (3), a rear encapsulation layer element (4) and a protective back layer element (5).

[0266] D. Storage stability test

[0267] D.1 Test 1

[0268] The film samples as described above were cut into three smaller pieces (300 x 50 x 0.45 mm) each time and placed in sealed aluminum bags, sealed PE bags, or stored at 23°C and 50% relative humidity without any packaging at all. Both bags were open to the atmosphere when the polymer was transferred into them. The MFR2 (190°C and 2.16 kg weight) of the samples was measured after different storage times, and the results are summarized in the following Table 4 and Figures 2 to 4(MFR2 versus time is shown). For CE1a to CE4a and IE1a, samples made from polymer compositions according to CE1 to CE4 and IE1, respectively, were used.

[0269] As shown in Table 4 below and Figures 2 to 4 It can be seen that, regardless of the sealing method used, the film made of polymer composition CE4 exhibits the worst storage stability. However, the combination of the stabilizer (= component (C)) used in CE4 and polymer A (= component (B)) shows excellent results, and the film made of the polymer composition shows the best storage stability. The experimental results clearly confirm that only the specific combination of the technical features of the first aspect of the embodiment of the present invention can obtain a polymer composition showing excellent storage stability.

[0270] Table 4: Results of storage tests.

[0271]

[0272] D.2 Test 2

[0273] Test Method

[0274] Storage Stability Measurements - Version 2

[0275] The film samples as described above were cut into three smaller pieces each time (300 x 50 x 0.45 mm) and placed in sealed aluminum bags. The samples were stored in an air circulating oven at 40°C. The MFR2 of the samples was measured after 3 and 7 days (190°C and 2.16 kg weight). The storage stability test was started six weeks after film extrusion. This is why the starting MFR values ​​were different. For Examples IE2a to IE5a, samples made from polymer compositions according to IE2 to IE5 were used.

[0276] result

[0277] Studying the results in Table 5 below, it can be seen that the MFR2 value decreases over time during storage when the concentration of Nucrel 0903 increases from 0.25 wt% (IE2a) to 1.25 (IE3a). When the polymer A content increases from 0.5 wt% (IE2a and IE3a) to 1.5 wt% (IE4a and IE5a), the MFR2 value decreases significantly slower over time.

[0278] Table 5: Results of storage tests.

[0279] unit IE2a IE3a IE4a IE5a <![CDATA[MFR2 (Start)]]> g / 10min 2.74 1.53 3.12 2.03 <![CDATA[MFR2 (3 days)]]> g / 10min 2.56 1.45 3.04 1.71 <![CDATA[MFR2 (7 days)]]> g / 10min 1.93 0.85 2.79 1.68

[0280] E.PID test

[0281] From Table 6 it can be concluded that the photovoltaic module comprising the front encapsulation layer element and the rear encapsulation layer element made of the polymer composition according to the invention exhibits only a small Pmax loss after the PID test. Furthermore, this conclusion is valid for the power retention of the front and rear sides of the bifacial module.

[0282] Table 6: Reserve power Pmax of PV modules 1 and 2.

[0283] Module 1 Module 2 Polymer composition for encapsulation layer element IE1 IE1 Retention Pmax 96h (front side) [%] a 99.10 99.68 Retention Pmax 96h (dorsal side) [%] a 98.35 99.95

[0284] a: Average value of 3 measurements.

Claims

1. A polymer composition (I), comprising at least the following components: (A) 87.00 to 99.79 wt% of a polymer selected from ethylene-vinyl acetate copolymers, polyolefin elastomers or ethylene polymers (a), based on the total weight of the polymer composition (I), wherein the ethylene polymer (a) is selected from (a1) an ethylene copolymer having units containing a functional group; (a2) an ethylene copolymer comprising one or more polar comonomer units selected from C1-C6 alkyl acrylate or C1-C6 alkylacrylate C1-C6 alkyl ester comonomer units, which carries a functional group-containing unit different from the polar comonomer unit; (a3) an ethylene copolymer comprising one or more α-olefin comonomer units; a functional group-containing unit having a different polar comonomer unit from the ethylene copolymer (a2); or a mixture thereof; wherein the functional group-containing unit of the ethylene polymer (a) is a silane group-containing unit (b); (B) 0.20 to 10.00 wt. % of an ethylene copolymer, based on the total weight of the polymer composition (I), containing units derived from at least one unsaturated carboxylic acid and / or anhydrides, metal salts, esters, amides or imides thereof and mixtures thereof, wherein component (B) is different from component (A); (C) 0.01 to 3.00 wt. % of a compound according to formula (a), based on the total weight of the polymer composition (I); and Optional components (B2) and / or components (D): (B2) a copolymer of ethylene and (meth)acrylic acid, wherein component (B2), if present, is different from components (A) and (B), (D) at least one additive selected from the group consisting of antioxidants, UV light stabilizers, metal deactivators, nucleating agents, clarifying agents, optical brighteners, acid scavengers, slip agents, pigments, fillers and flame retardants, tackifiers, plasticizers, crosslinking agents, crosslinking enhancers, wavelength conversion agents and mixtures thereof, Components (A), (B) and (C) and, if present, component (B2) and / or component (D) add up to 100% by weight.

2. The polymer composition (I) according to claim 1, characterized in that Component (A) includes the following: (a1) an ethylene copolymer having a silane group-containing unit (b) as a functional group-containing unit; or (a2) an ethylene copolymer comprising one or more polar comonomer units selected from C1-C6 alkyl acrylate or C1-C6 alkylacrylate C1-C6 alkyl ester comonomer units, which carries a unit (b) containing a silane group as a functional group-containing unit different from the polar comonomer unit.

3. The polymer composition (I) according to claim 2, characterized in that Component (A) is (a1) an ethylene copolymer having a silane group-containing unit (b) as a functional group-containing unit; or (a2) an ethylene polymer comprising methyl acrylate comonomer units, which carries a silane group-containing unit (b) as a functional group-containing unit different from the polar comonomer unit.

4. The polymer composition (I) according to claim 2, characterized in that Component (A) is an ethylene copolymer (a1) having vinyltrimethoxysilane comonomer units or an ethylene terpolymer (a2) having methyl acrylate comonomer units and vinyltrimethoxysilane comonomer units.

5. The polymer composition (I) according to claim 2, characterized in that Component (A) is different from the polyolefin elastomer and / or the ethylene-vinyl acetate copolymer.

6. The polymer composition (I) according to any one of claims 1 to 5, characterized in that Component (B) is a copolymer of ethylene and a C4 to C10 alpha olefin comonomer; wherein the copolymer has (i) Measured according to ISO 1183 at 850 kg / m 3 Up to 920kg / m 3 density within the range of; and / or (ii) MFR2 in the range of 0.1 to 20.0 g / 10 min, measured according to ISO 1133 at 190°C and a load of 2.16 kg.

7. The polymer composition (I) according to claim 6, characterized in that Component (B) is a copolymer of ethylene and 1-octene.

8. The polymer composition (I) according to any one of claims 1 to 5, characterized in that Component (B) carries functional group-containing units derived from a compound selected from the group consisting of maleic anhydride, acrylic acid, methacrylic acid, crotonic acid, fumaric acid, fumaric anhydride, maleic acid, citraconic acid, and mixtures thereof; and / or Component (B) is obtained by copolymerizing and / or grafting an ethylene copolymer with a compound selected from the group consisting of maleic anhydride, acrylic acid, methacrylic acid, crotonic acid and mixtures thereof, and / or The content of the functional group-containing unit derived from an unsaturated carboxylic acid or a carboxylic acid anhydride in component (B) is in the range of 0.01 to 2.0% by weight.

9. The polymer composition (I) according to claim 8, characterized in that Component (B) is obtained by grafting an ethylene copolymer with maleic anhydride.

10. The polymer composition (I) according to any one of claims 1 to 5, characterized in that Component (C) is a compound represented by formula (a); wherein: R1 and R 1’ are each independently a n-alkyl group; and / or R2 and R 2’ are each independently an n-alkyl or cycloalkyl group; and / or X is selected from the group consisting of secondary amines and tertiary amines.

11. The polymer composition (I) according to any one of claims 1 to 5, characterized in that The molecular weight of component (C) is in the range of 1000 g / mol to 2800 g / mol; and / or Component (C) is a compound having the following formula (b):

12. The polymer composition (I) according to any one of claims 1 to 5, characterized in that The polymer composition (I) comprises the component (B2) in an amount ranging from 0.05 to 5 wt % based on the total weight of the polymer composition (I); Components (A), (B), (C) and (B2) and, if present, component (D) add up to 100% by weight.

13. The polymer composition (I) according to any one of claims 1 to 5, characterized in that The polymer composition (I) comprises the at least one additive (D) in an amount ranging from 0.0001 to 10 wt % based on the total weight of the polymer composition (I); Components (A), (B), (C) and additive (D) and, if present, component (B2) add up to 100% by weight.

14. The polymer composition (I) according to any one of claims 1 to 5, characterized in that The content of component (A) in the polymer composition (I) is in the range of 92.5 to 99.45 wt % based on the total weight of the polymer composition (I); and / or The content of component (B) in the polymer composition (I) is in the range of 0.50 to 5.00 wt % based on the total weight of the polymer composition (I); The content of component (C) in the polymer composition (I) is in the range of 0.05 to 2.50 wt % based on the total weight of the polymer composition (I).

15. A photovoltaic module comprising at least one layer comprising the polymer composition (I) according to any one of claims 1 to 14.

16. The photovoltaic module according to claim 15, characterized in that: The photovoltaic module comprises a front encapsulation layer element and a rear encapsulation layer element, wherein at least one of the front encapsulation layer element and the rear encapsulation layer element comprises the polymer composition (I); and / or The polymer composition (I) does not crosslink in the presence of a peroxide or a silanol condensation catalyst selected from carboxylates of tin, zinc, iron, lead or cobalt or aromatic organic sulfonic acids; and / or The protective front element is a rigid protective front element; and / or The protective backing member is a rigid protective backing member.

17. The photovoltaic module according to claim 15 or 16, characterized in that: The retention P of the photovoltaic module determined according to IEC 60904 max Above 95%.

18. A method for improving the storage stability and / or transportation stability of a polymer (A), comprising the following steps: a) providing a polymer (A), wherein the polymer (A) is selected from ethylene-vinyl acetate copolymers, polyolefin elastomers or ethylene polymers (a), wherein the ethylene polymers (a) are selected from (a1) an ethylene copolymer having units containing a functional group; (a2) an ethylene copolymer comprising one or more polar comonomer units selected from C1-C6 alkyl acrylate or C1-C6 alkylacrylate C1-C6 alkyl ester comonomer units, which carries a functional group-containing unit different from the polar comonomer unit; (a3) an ethylene copolymer comprising one or more α-olefin comonomer units; a functional group-containing unit having a different polar comonomer unit from the ethylene copolymer (a2); or a mixture thereof; and wherein the functional group-containing unit of the ethylene polymer (a) is a silane group-containing unit (b); b) providing an ethylene copolymer (B) having functional group-containing units derived from at least one unsaturated carboxylic acid and / or anhydrides, metal salts, esters, amides or imides thereof and mixtures thereof, wherein component (B) is different from component (A); c) providing a compound according to formula (a); d) mixing polymer (A) with components (B) and (C), optionally the following component (B2) and / or component (D) to obtain a stabilized polymer composition (I): (B2) a copolymer of ethylene and (meth)acrylic acid, wherein component (B2), if present, is different from components (A) and (B), (D) at least one additive selected from the group consisting of antioxidants, UV light stabilizers, metal deactivators, nucleating agents, clarifying agents, optical brighteners, acid scavengers, slip agents, pigments, fillers and flame retardants, tackifiers, plasticizers, crosslinking agents, crosslinking enhancers, wavelength conversion agents and mixtures thereof, Components (A), (B) and (C) and, if present, component (B2) and / or component (D) add up to 100% by weight.

19. The method according to claim 18, characterized in that Component (A) includes the following: (a1) an ethylene copolymer having a silane group-containing unit (b) as a functional group-containing unit; or (a2) an ethylene polymer comprising methyl acrylate comonomer units, which carries a unit (b) containing a silane group as a functional group-containing unit different from the polar comonomer unit; and / or; Component (B) is a copolymer of ethylene and a C4 to C10 alpha olefin comonomer; wherein the copolymer has (i) Measured according to ISO 1183 at 850 kg / m 3 Up to 920kg / m 3 density within the range of; and / or (ii) an MFR2 in the range of 0.1 to 20.0 g / 10 min measured at 190°C and a load of 2.16 kg according to ISO 1133; and / or Component (C) is a compound having the following formula (b):

20. The method according to claim 19, characterized in that Component (B) is a copolymer of ethylene and 1-octene.

21. Use of a polymer composition (I) according to any one of claims 1 to 14 in at least one layer of a photovoltaic module.

Citation Information

Patent Citations

  • Photovoltaic encapsulating material with high light transmittance

    CN108517188A

  • Olefin-based ionomer resin composition

    US20140045990A1

  • Elastomer of an ethylene copolymer cross-linked with an unsaturated acid or anhydride

    US3236917A

  • Extruding process for preparing functionalized polyolefin polymers

    US4639495A

  • Maleic anhydride grafts of olefin polymers

    US4950541A